Brand Loyalty in Smartphone in Nepal - Karki, Amisha (Nepalese Journal of Management, 2025)
This study analyzed on the brand loyalty in smartphone in Nepal. The dependent variable is brand loyalty. Similarly, the selected independent variables are price and value proposition, customer service and support, social influence and word of mouth, brand communication and marketing, and eco system and integration. The primary source of data is used to assess the opinions of the respondents regarding price and value proposition, customer service and support, social influence and word of mouth, brand communication and marketing, and eco system and integration in Nepal. The study is based on primary data of 151 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of brand loyalty in smartphone in Nepal. The study showed that price and value proposition is positively correlated to brand loyalty. It indicates that better price and value proposition, leads to better brand loyalty. Similarly, customer service and support is positively related to brand loyalty indicating that higher the level of customer service and support, higher would be the brand loyalty. Likewise, social influence and word of mouth has positive relationship with brand loyalty. It shows that social influence and word of mouth leads to an increase in the brand loyalty. Similarly, brand communication and marketing has positive relationship with brand loyalty. It reveals that higher the level of brand communication and marketing, higher would be brand loyalty. The result shows that there is positive relationship between eco system and integration and brand loyalty. It shows that an increase in the level of eco system and integration leads to the increase in the brand loyalty.